NILAI GENDER DALAM MATERI PEMBELAJARAN BAHASA ARAB KELAS X SMA MUHAMMADIYAH BANTUL SUATU KAJIAN SOSIOLINGUISTIK - Nurarsyi Nugrahawati; Agung Setiyawan (El-Tsaqafah : Jurnal Jurusan PBA, 2025)
This study aims to analyze gender values in Arabic language learning materials for tenth-grade students at SMA Muhammadiyah Bantul using a sociolinguistic approach. The research employs a qualitative approach with a literature review, and data analysis is conducted using the interactive technique of Miles and Huberman. The analysis was carried out on several chapters of the learning materials. The results indicate the presence of gender bias in the presentation of Arabic language learning materials for tenth-grade students at SMA Muhammadiyah Bantul. After being analyzed based on five forms of gender inequality, it was found that seven chapters in the learning materials exhibit gender bias in the forms of stereotypes, marginalization, and subordination. Meanwhile, only one chapter, ???? ????, does not show any indications of gender bias. This imbalance is evident in various aspects, such as the dominance of male characters in dialogue texts, vocabulary choices that predominantly represent male roles in the public sphere, and the lack of female involvement in academic and professional discourse. Additionally, there is a tendency to associate certain roles with specific genders, which can reinforce stereotypes among students.